2007
DOI: 10.1143/jjap.46.1921
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reaction of TiN/HfSiON Gate Stack in High-Temperature Annealing for Gate-First Metal–Oxide–Semiconductor Field-Effect Transistors

Abstract: A recently developed procedure for solving the stationary Schrodinger equation in matrix representation form is proved to be useful in calculating quasibound energy levels. Results for a simple quantum mechanical model with potential energy function V =r-' + Ar ( A < 0) are shown to be very accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This, in turn, may disturb the in and out diffusion process that takes place in the device particularly at interfaces and towards the bulk and hence provides a sudden shift in the resistivity/conductivity behavior at a higher annealing temperature. Such behavior and trends in form of measurement profile for these structures are known and discussed in related studies [18][19][20]. Electrical measurements were performed to determine the resistance of the atomic layer deposited TiN thin films.…”
Section: Resultsmentioning
confidence: 94%
“…This, in turn, may disturb the in and out diffusion process that takes place in the device particularly at interfaces and towards the bulk and hence provides a sudden shift in the resistivity/conductivity behavior at a higher annealing temperature. Such behavior and trends in form of measurement profile for these structures are known and discussed in related studies [18][19][20]. Electrical measurements were performed to determine the resistance of the atomic layer deposited TiN thin films.…”
Section: Resultsmentioning
confidence: 94%
“…2,3 However, it has been reported that high-k species such as Hf and La atoms can diffuse even into gate electrodes during high-temperature annealing. [4][5][6] Our previous study, focusing on the La-induced interface dipole in TiN/HfLaSiO/SiO 2 /Si gate stacks, showed the upward diffusion of La at temperatures above 900 C, at which point the SiO 2 underlayer thickness increased. 7 On the basis of this result, we speculated that the upward diffusion is driven by SiO 2 growth and can thus be suppressed by hampering this growth.…”
mentioning
confidence: 94%
“…In addition to interfacial SiO 2 growth, it has been reported that metal elements such as Hf and La atoms in high-k layers diffuse into gate electrode after high-temperature activation annealing [1][2][3][4]. Consequently, a loss of leakage reduction merit due to permittivity lowering of Hf-based high-k layer has been pointed out [4].…”
Section: Introductionmentioning
confidence: 99%